Aspects for efficient wide spectral band THz generation via CO2 laser down conversion - Panchenko Yu. N. Yury Nikolaevich; Andreev Yu. M. Yury Mikhaylovich; Lansky G. V. Grigory Vladimirovich; Losev V. F. Valery Fedorovich; Lubenko D. M. Dmitry Mikhaylovich (2015, 2015)
Title screen